Biomechanical and neuromuscular strategies on backward somersault landing in artistic gymnastics: A case study - Chengliang Wu; Weiya Hao; Wei He; Xiaofei Xiao; Xuhong Li; Wei Sun (Mathematical Biosciences and Engineering, 2019)
Landing is a crucial factor in gymnastics competitions, but the underlying biomechanical and neuromuscular strategies remains unclear. This study aimed to investigate the biomechanical characteristics and neuromuscular strategies of landing for backward somersault. A 19-segment human model was developed and bilateral lower-limb joint loadings were estimated using computer stimulation. Bilateral lower-limb joint angles, vertical ground reaction force (vGRF), impulse, joint reaction force, joint torque, power, work, stiffness and electromyogram (EMG) of the rectus femoris, biceps femoris, tibialis anterior, and lateral gastrocnemius were presented during initial (touchdown to peak vGRF) and terminal impact-phases of landing (peak vGRF to vGRF equaling to body weight). The hip, knee, and ankle joints were rapidly flexed (8°, 20°, and 18°, respectively) during initial impact-phase and maintained at around 90°, 120°, and 60°, respectively terminal impact-phase. Flexor and extensor torques were demonstrated for lower-limb joints during initial and terminal impact-phases, respectively. The stiffness of lower limb joints and the EMGs amplitude of all examined muscles during terminal impact-phase were several times larger than that during initial impact-phase. The absolute symmetry indexes were less than 10% for lower limb joint angles and larger than 10% for the kinetics and muscle activation. The findings demonstrated symmetrical motion for lower limb joints with flexing rapidly at initial impact-phase and maintaining unchanged at terminal impact-phase and asymmetry in joint loading and muscle activation during landing.